Development of an integrated hybrid solar thermal power system with thermoelectric generator for desalination and power production - Demir, Murat Emre; Dincer, Ibrahim (ELSEVIER, 2017)
In this study, an integrated system for desalinated water and electricity production is developed and thermodynamically analyzed. The proposed system consists of a solar-natural gas hybrid power plant, thermoelectric generator (TEG), Rankine cycle to produce electricity and flash distillation unit to produce fresh water. The proposed electricity-fresh water co-generation plant uses solar driven volumetric pressurized air receivers as main power supply and uses natural gas to compensate power when the direct normal irradiance is below 900 W/m(2). Thermoelectric materials are used to generate electricity from waste heat of gas turbine. Flash distillation unit is used to produce fresh water from seawater by the waste heat of Rankine cycle. All thermodynamic quantities, such as energy and exergy efficiencies, exergy destructions are calculated for all system components. The combustion reaction is modelled on ASPEN Plus software package. TEG unit is modelled on COMSOL Multiphysics software package, and the rest of the elements of the system are analyzed in the Engineering Equation Solver (EES). The overall exergy and energy efficiencies of the system are deterinined to be 54.9% and 44.5% respectively Where the total energy input comes 50% from solar system and 50% from natural gas. The results show that TEG unit can generate power more than 32 kW by using the waste heat. The present results indicate that it is possible to produce 3.36 kg/s of fresh water from proposed system. Furthermore, the effects of direct normal irradiance level, ambient wind speed, seawater temperature, various cool side cooling options for the thermoelectric generator on the system performance are investigated. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Desalination; Power generation; Thermoelectric generator; Volumetric solar receiver; Solar gas turbine; Exergy efficiency; Flash distillation; PARABOLIC-TROUGH; ENERGY; HEAT; DESIGN; PLANTS; Engineering; Water Resources